2014
DOI: 10.1097/01.ogx.0000442828.54138.67
|View full text |Cite
|
Sign up to set email alerts
|

A 2-Stage Ovarian Cancer Screening Strategy Using the Risk of Ovarian Cancer Algorithm (ROCA) Identifies Early-Stage Incident Cancers and Demonstrates High Positive Predictive Value

Abstract: BACKGROUND A 2‐stage ovarian cancer screening strategy was evaluated that incorporates change of carbohydrate antigen 125 (CA125) levels over time and age to estimate risk of ovarian cancer. Women with high‐risk scores were referred for transvaginal ultrasound (TVS). METHODS A single‐arm, prospective study of postmenopausal women was conducted. Participants underwent an annual CA125 blood test. Based on the Risk of Ovarian Cancer Algorithm (ROCA) result, women were triaged to next annual CA125 test (low risk),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
33
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 0 publications
0
33
0
Order By: Relevance
“…6 The ROCA is now being evaluated as a first-line screen prompting TVS as a second-line screen, as a part of a multimodal screening (MMS) strategy in the United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) 7 and in the Normal Risk Ovarian Cancer Screening Study (NROSS) in the United States. 8 With each new CA125 test, a ROCA score is calculated, and women are triaged into a lowrisk group (annual CA125 screening referral), intermediaterisk group (3-month repeat CA125 referral), and a high-risk group (referral to TVS and a gynecological oncologist and, if necessary, surgery). 7 Triaging is revised based on the new ROCA score for every new CA125 result.…”
mentioning
confidence: 99%
“…6 The ROCA is now being evaluated as a first-line screen prompting TVS as a second-line screen, as a part of a multimodal screening (MMS) strategy in the United Kingdom Collaborative Trial of Ovarian Cancer Screening (UKCTOCS) 7 and in the Normal Risk Ovarian Cancer Screening Study (NROSS) in the United States. 8 With each new CA125 test, a ROCA score is calculated, and women are triaged into a lowrisk group (annual CA125 screening referral), intermediaterisk group (3-month repeat CA125 referral), and a high-risk group (referral to TVS and a gynecological oncologist and, if necessary, surgery). 7 Triaging is revised based on the new ROCA score for every new CA125 result.…”
mentioning
confidence: 99%
“…A recent prospective study validated the high PPV (40 %) and specifi city (99.9 %) using ROCA. Additionally, early stage cancers were detected (stage I or II) [ 146 ].…”
Section: Early Detection Of Eaocmentioning
confidence: 99%
“…However, ROC and ROCA are very promising. [29][30][31] Keeping a record with a symptom index (non-specific abdominal pain, sensation of abdominal distention, constipation alternating with diarrhea, rectal tenesmus, pelvic sore, and feeling of early satiety) did not reach a predictive value of 10. Even so, it is suggested that the patient should have a TVUS every 6 months and the measuring of CA 125 in case of having these symptoms more than 12 times a month.…”
Section: Eoc Early Detectionmentioning
confidence: 99%